Application of Naïve Bayes to Diagnose Health in Bodybuilding Athlete - Maulina Tria Audina Gultom; Yuni, Rahma (Journal of Computer Science and Informatics Engineering, 2023)
Injury is a structural damage to body function due to coercion of physical pressure can also be chemical. Self-injury due to disruption of normal anatomy and function caused by a pathological condition. Physical injury occurs when the human body experiences a sudden decrease in energy in an amount that exceeds the physiological tolerance threshold due to a deficiency of one or more essential elements such as oxygen. Minor injuries that go unnoticed for years have long-term consequences. Most foot problems are chronic and can affect the position of the bones if a foot injury is not treated quickly. Damaged bone can cause inflammation of the surrounding muscles, and because the muscles are surrounded by a tight membrane this condition can restrict blood supply which in the worst case results in muscle death (necrosis). There are still many people who don't know how to deal with foot injuries. There fore researchers developed an expert system for diagnosing foot injuries using the Naive Bayesian method to help people get information about foot injuries and find solutions to overcome them. This system makes it easier for people to know the symptoms of foot injuries. Keywords: Bodybuilder, Injury, Naive Bayes